Propolis for the treatment of onychomycosis - Flavia Franco Veiga; Maiara Ignacio Costa; Erika Seki Kioshima Cótica; Terezinha Inez Estivalet Svidzinski; Melyssa Negri (Wolters Kluwer Medknow Publications, 2018)
Onychomycosis is a fungal nail infection, considered as a public health problem because it is contagious and it interferes with the quality of life. It has long and difficult treatment, with many side effects and high cost. Propolis extract (PE) is a potential alternative to conventional antifungal agents because it has low cost, accessibility, and low toxicity. Herein, we report the favorable response of PE in onychomycosis in three elderly patients.